The value of marriage in Singapore. - Koh, Mi Zhi Mitzi. (2012)
With persistent trends of delayed marriages and declining marriage rates, it is important to find a value for marriage to investigate the attitudes of different groups hold towards marriage in Singapore. We conducted a survey using the Contingent Valuation Method (CVM) to elicit the monetary values for Willingness-to-pay (WTP) to get a suitable partner and for a marriage. 400 Singaporeans and Singapore Permanent Residents who are single and between the ages of 20-34 were interviewed face-to-face in public areas. The values and attitudes of the singles in Singapore are found to be generally sound. Financial stability, career progression and cost of living are also found to be the major factors in marriage decisions. The mean WTP estimated for partner is S$3,359.30, whereas the mean WTP estimated for marriage is S$7,681.23. The low value of marriage as seen from the mean WTP for marriage could be a reason that explains why marriage rate is declining. The WTP for finding a suitable partner is observed to be positively related to the type of house ownership, the income, overtime work hours and care giving responsibilities while the WTP for marriage is observed to be positively related to educational level and care giving responsibilities. Beyond the scope of this project, we propose for further research to be conducted in different countries to enable a cross-country comparison which seeks to explore the differences in WTP values for marriage across different countries.